A case of unilateral epidermal nevi complicated by atopic dermatitis treated with dupilumab - Nagatsuka, Yumi; Nakashima, Chisa; Kitayama, Naomi; Ishida, Yoshio; Kabashima, Kenji; Otsuka, Atsushi (Trends in Immunotherapy, 2024)
Epidermal Nevus Syndrome (ENS) is a congenital disorder characterized by skin lesions called epidermal nevi. This condition typically appears at birth or in infancy. However, a case of adult‐onset epidermal nevi was reported in a 36‐year‐old male with a history of atopic dermatitis (AD) and skin abnormalities on the right side of his body. He had been using topical steroids for AD but eventually started dupilumab treatment at age 41. The treatment led to significant improvements in his skin condition, including a reduction in erythema and scaling. Laboratory tests also showed improvement in serum Immunoglobulin E (IgE) levels and other markers. We report with a literature review.